2012
DOI: 10.1007/s13139-011-0125-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Diagnosis of Carcinoma of the Bladder Due to Uptake of 99mTc-MDP

Abstract: An 80-year-old male patient presented to the orthopaedist for evaluation of low backache. A bone scan was performed using 740 MBq (20 mCi) 99m Tc-MDP. Wholebody planar images were acquired 3 h after injection (Fig. 1). The scan revealed normal physiological tracer uptake in skeletal system but irregular and heterogenous accumulation of tracer in the bladder (Fig. 2). To evaluate this abnormal accumulation further, the patient was given a dose of 40 mg furosemide and asked to drink plenty of water. He was instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This case demonstrated that vertical appearance of urinary bladder on bone scintigraphy might not always suggest adjacent pathology. Using SPECT/CT imaging to investigate the abnormal bladder shape could be helpful for accurate image interpretation 9–13 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This case demonstrated that vertical appearance of urinary bladder on bone scintigraphy might not always suggest adjacent pathology. Using SPECT/CT imaging to investigate the abnormal bladder shape could be helpful for accurate image interpretation 9–13 …”
mentioning
confidence: 99%
“…Using SPECT/CT imaging to investigate the abnormal bladder shape could be helpful for accurate image interpretation. [9][10][11][12][13]…”
mentioning
confidence: 99%